2009
DOI: 10.1007/s00122-009-1234-8
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping the soybean aphid resistance gene Rag1 in soybean

Abstract: The soybean aphid (Aphis glycines Matsumura) is an important soybean [Glycine max (L.) Merr.] pest in North America. The dominant aphid resistance gene Rag1 was previously mapped from the cultivar 'Dowling' to a 12 cM marker interval on soybean chromosome 7 (formerly linkage group M). The development of additional genetic markers mapping closer to Rag1 was needed to accurately position the gene to improve the eVectiveness of markerassisted selection (MAS) and to eventually clone it. The objectives of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 36 publications
0
70
0
Order By: Relevance
“…The difference or similarity of action between dominant and recessive aphid resistance genes in soybeans remains to be investigated. The QTLs detected in this study are located in similar genomic regions as Rag1 on chromosome 7 (Li et al 2007, Kim et al 2010 and Rag3 on chromosome 16 (Zhang et al 2010). Although the two resistant genes in PI 567598B were considered recessive (Mensah et al 2008), and Rag1 or Rag3 was considered dominant or co-dominant (Hill et al 2006a;Zhang et al 2010), they may still be the same genes as Rag1 and Rag3, since the susceptible parent in this study was different from the ones used for characterizing Rag1 and Rag3.…”
Section: Discussionmentioning
confidence: 79%
“…The difference or similarity of action between dominant and recessive aphid resistance genes in soybeans remains to be investigated. The QTLs detected in this study are located in similar genomic regions as Rag1 on chromosome 7 (Li et al 2007, Kim et al 2010 and Rag3 on chromosome 16 (Zhang et al 2010). Although the two resistant genes in PI 567598B were considered recessive (Mensah et al 2008), and Rag1 or Rag3 was considered dominant or co-dominant (Hill et al 2006a;Zhang et al 2010), they may still be the same genes as Rag1 and Rag3, since the susceptible parent in this study was different from the ones used for characterizing Rag1 and Rag3.…”
Section: Discussionmentioning
confidence: 79%
“…Both Rpg1-b and the third gene are outside the 54-kb region containing Rag2, so they are likely not Rag2. Our research on fine mapping Rag1 also showed that the 115-kb region including Rag1 contains two NBS-LRR genes (Kim et al 2010). These gene predictions for the Rag2 region are all based on the Williams 82 sequence and Williams 82 does not contain (Tamulonis et al 1997).…”
Section: Discussionmentioning
confidence: 53%
“…Thus, these putative R genes could be strong candidates for the major foxglove aphid resistance gene, Raso2. Among the previously reported soybean R genes, Rag1, soybean aphid resistance gene, was mapped to 115 kbp on chromosome 7 that corresponds to Raso2, and there are two candidate NBS-LRR genes in the Rag1 interval (Kim et al 2010a). However, the gene source of Rag1, cultivars 'Jackson' and 'Dowling', did not show the resistance responses to Korea biotype foxglove aphid in Fig.…”
Section: Discussionmentioning
confidence: 99%